Effects of aerobic training with blood flow restriction on aerobic capacity, muscle strength, and hypertrophy in young adults: a systematic review and meta-analysis - Gao, Zhendong; Li, Yan; Zhang, Jinjin; Li, Liqiang; Wang, Tao; Wang, Xiaolin; Wang, Hao (Frontiers in Physiology, 2025)
Aerobic training with blood flow restriction (AT-BFR) has shown promise in enhancing both aerobic capacity and exercise performance. The aim of this review was to systematically analyze the evidence regarding the effectiveness of this novel training method on aerobic capacity, muscle strength, and hypertrophy in young adults. Studies were identified through a search of databases including PubMed, Scopus, Web of Science, SPORTDiscus, CINAHL, Cochrane Library, and EMBASE. A total of 16 studies, involving 270 subjects, were included in the meta-analysis. The results revealed that AT-BFR induced greater improvements in VO2max (SMD = 0.27, 95%CI: [0.02, 0.52], p < 0.05), and muscle strength (SMD = 0.39, 95%CI: [0.09, 0.69], p < 0.05), compared to aerobic training with no blood flow restriction (AT-noBFR). However, no significant effect was observed on muscle mass (SMD = 0.23, 95%CI: [-0.09, 0.56], p = 0.162). Furthermore, no moderating effects on the outcomes were found for individual characteristics or training factors. In conclusion, AT-BFR is more effective than AT-noBFR in improving aerobic capacity and muscle strength, making it a promising alternative to high-intensity training.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024559872.